MODIFIKASI DAN PENGUJIAN SISTEM DISTILASI UNTUK MEMISAHKAN PROPANA DARI N-BUTANA DAN I-BUTANA DENGAN BAHAN BAKU LPG (LPG DEPROPANIZER) - Hasanuddin
The goal of this distillation research is to separate propane from n-butane and i-butane by feeding LPG into a distillation column. The basic components resulted from the separation will be used to make hydrocarbon refrigerant that is environment-friendly. The distillation system design in this research uses Hengstebeck diagram to determine the number of stage and feed position. The energy consumption in the separation process is quite high on reboiler and condensor. It is anticipated by using a heat pump that pumps energy from condensor to reboiler. This research uses a heat pump for low temperature distillation by using external refrigerant (HCR-12). In the initial test without auxiliary condensor, the compressor discharge pressure on a heat pump is quite high. It is limited by using pressure switch controlled by data acquisition, so the compressor operates discontinuously. The next test uses auxiliary condensor on a heat pump to reject heat from compressor, so pressure discharge does not exceed the limited pressure and the compressor operates continuously. The test on product sample by measuring the saturation pressure at different level temperatures and by comparing with graph from refprop ver. 6.01 of NIST shows 0.7 mole of propane separation at distillate from the expected result of 0.95. This is affected by vaporizing temperature at the bottom column, which achieves only 44°C from the expected 49°C. Additionally, condensing temperature can only achieve 21°C from the expected 11°C. This research shows the maximum separation has not been achieved. Therefore, further modification is required on a thermal pump to achieve a maximum separation. Modification that must be made to reduce fan speed on auxiliary condensor, to isolate reflux and reboiling pipe, as well as bottom and distillate product pipe.